Improving student understanding through interactive e-books on environmental education in the biology education study program at pattimura university - Advend Sri Rizki Sianturi; Sendy Putra Pradana (12 Waiheru, 2025)
Environmental education plays a crucial role in raising students' awareness of the importance of environmental conservation. However, the learning process in the Biology Education Study Program at Universitas Pattimura still faces challenges, particularly the lack of practical and contextual learning materials. This study aims to develop a contextual-based interactive e-book integrated with waste management practice guidelines to enhance students’ understanding and engagement with local environmental issues. This qualitative research was conducted in May 2025, involving second-semester biology education students. The e-book development followed the adapted Borg & Gall development model. The e-book contains topics on the natural resource potential of Maluku, environmental problems, management strategies, and field practice guides. Trial results showed highly positive student responses, with an average acceptance rate of 86.22%. Students’ understanding scores increased significantly, from a pre-test average of 62.4 to a post-test average of 85.1, with a paired t-test indicating a statistically significant improvement (p < 0.0001). Additionally, 92% of students stated that the material was easier to understand because it related directly to their daily environment. In conclusion, this interactive e-book has proven effective as a contextual learning medium that improves students' comprehension, participation, and practical skills in sustainable environmental management. It also supports the vision of the study program to produce environmentally literate and competent graduates.